Biology Students’ Morality When Engaged With Moral Dilemmas in the Human-Nature Context - van der Leij, Tore; Avraamidou, Lucy; Wals, Arjen; Goedhart, Martin (Frontiers in Education, 2021)
Framed within the Four Component Model (FCM) of morality, this case study investigates the nature of (nationality) 15-16 years old biology students’ morality in socioscientific issues in the human-nature context. In doing so, we discuss the morality of 12 students with data collected through individual semi-structured interviews following the implementation of a specially-designed curriculum. During the interviews the students discussed a moral dilemma related to the rehabilitation of seals. The findings indicate that students demonstrated aspects of all four FCM components. The students placed themselves in the perspectives of involved stakeholders, both affectively and cognitively. In addition, the students exhibited both rationality-based and emotion-based moral reasoning. A number of students experienced an ‘inner conflict’ between cognitive and emotional reasoning, which affected their moral motivation and – as such – represented their moral reflection process. Students’ moral emotions were often decisive in their moral decision-making. Among the different kinds of moral emotions (compassion, guilt, duty, respect), compassion appeared most. The findings are discussed alongside implications for future research with a focus on encouraging aspects of students’ morality, which are an important part of citizenship skills.